Implemento de trator para auxílio na poda de brotos de árvore em altura - Napolitano, Pedro (Universidade Federal de São Carlos, 2020)
Due to growing concerns about the environment, consumption of legal timber relies on so-called reforestation timber, whose origin is from planted trees for this specific need. In order to make this plantation more efficient and profitable, one of the commonly used procedures is sprout (new and small branches) pruning. While the trees are shorter than 5 meters, the process can be done using special shears or saws with extenders. However, after they grow beyond this point, pruning becomes dependent on high-cost and high-complexity agricultural implements. Thus, there is the possibility of developing a new mechanism that establishes itself in the middle of this spectrum, meeting the current demand. In the face of this need, this project contemplates the conception of an integrated solution, made of simple commercial elements that are already available in the market, such as telescopic extenders and circular saw. The arrange will allow the development of the project of a semiautomatic implement whose function is to help sprouts pruning in greater heights, being simple and accessible financially. Therefore, an operator is capable of choosing which sprouts need to be cut and perform the procedure in variable heights until 12 meters with the aid of an accessible, simple and functional equipment.
Agricultural implement for aid in tree pruning in elevation
Keywords: Implemento agrícola para poda; Maquinário para poda de árvore; Implemento para remoção de brotos de árvore; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::MERCADOLOGIA; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO